A guide to sleep problems and solutions in the early years. (2nd December 2020) - Hancock, David
Abstract : Sleep problems in children can be distressing for parents who may require practical, emotional and psychological support to help their child to sleep. A study reported that 10% of children are found to have a sleep problem at any given point during early childhood, and that problems persist in a significant minority of children throughout early development. This article considers the sleeping problems experienced during the early years, with some advice about how parents can prevent or resolve them.